Attribution of changes in the water balance of a basin to land-use changes through combined modelling of basin hydrology and land-use dynamics. Issue 11 (16th November 2022) - Gunacti, Mert Can; Kandemir, Fulya Aydin; Najar, Mohamed; Kuzucu, Aysegul; Uyar, Meltem; Barbaros, Filiz; Boyacioglu, Hulya; Gul, Gulay Onusluel; Gul, Ali
Abstract: Land use and land cover change (LULCC) is considered one of the major drivers of climate change, although climate change can also foster direct or indirect influences leading to LULCC. The objective of the presented study is to offer a strategic observation frame as the land use and land cover (LULC) transitions are grouped to define the cover flows (CFs). The Küçük Menderes River Basin (KMRB), which is located in the west of Turkey was examined as the case study. Through LULCC modelling via the employment of multi-layer perceptron (MLP), cellular automata (CA), and Markov Chain methods, future LULC maps were projected up to the horizon of 2050. Hydrologic responses of the basin to LULCC were determined by the developed hydrologic model, which is generated by the Soil and Water Assessment Tool (SWAT). The superimposed impacts of the examined effects of LULCC have been investigated by the CF types. This way, the individual impacts of the CFs have been assessed. In the case of the KMRB, projected annual runoffs for the year 2050 cover map represent a 9.06% reduction and the major responsible CF type for this reduction is the conversion from forest to non-irrigated agricultural land cover by 22.90%. HIGHLIGHTS: Future water availability of the KMRB is investigated by the defined cover flows. About a 9% reduction in surface water volume is expected by the year 2050 at the KMRB outlet. Conversion to non-irrigated agriculture is the major cause of the water volume reduction in the basin. Graphical Abstract